2017
DOI: 10.1186/s12889-017-4983-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sitting height, sitting height to height ratio with blood pressure among Polokwane private school children aged 6–13 years

Abstract: Background: It is notable that sitting height (SH) correlates with blood pressure (BP) in children and adolescents of developed countries. However, little is known about the relationships between SH and SH to height ratio (SH/H) with BP in South African children from middle and upper socio-economic groups. The purpose of this study was to compare SH and SH/H of private school attending children in the Polokwane area with National Health and Nutrition Examination Survey III (NHANES III) reference population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Greater height, SH and SH/H in children and adolescents have been shown to positively influence blood pressure. Studies performed in China [17], Brazil [19] and rural South Africa [21] indicated that height, SH and SH/H ratio are associated with blood pressure. This is in line with our study, where it was observed that height, SH and SH/H were significantly associated with SBP in the unadjusted analysis, and height alone was significantly associated with SBP in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Greater height, SH and SH/H in children and adolescents have been shown to positively influence blood pressure. Studies performed in China [17], Brazil [19] and rural South Africa [21] indicated that height, SH and SH/H ratio are associated with blood pressure. This is in line with our study, where it was observed that height, SH and SH/H were significantly associated with SBP in the unadjusted analysis, and height alone was significantly associated with SBP in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…among Brazilian [19], South African [21] and Indian [25] children found that SH was associated with BP. Furthermore, a study by Dong et al [17] in Chinese children and adolescents found that SH correlated positively with BP.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…But, given the shorter stature of individuals with Down syndrome, it is possible that we underestimated their blood pressure in contrast to the controls. However, trunk size is the main determinant of blood pressure association with height, as opposed to leg length [51,52], and since trunk size is fairly similar in Down syndrome compared to healthy controls (i.e., shorter leg length is primary cause of shorter stature in Down syndrome), underestimation of blood pressure in our cases is likely minimal [53,54]. We used the Schwartz formula to estimate GFR in our participants with Down syndrome, which may decrease the accuracy of the eGFR in Down syndrome, as creatinine production may be altered [55].…”
Section: Limitationsmentioning
confidence: 99%